Role Of Political Parties In Resolving The Challenges Confronting Nigeriafrom 1960-1966 - Mas’ud Bello; Sani Ibrahim (International Studies Journal)
Shortly after Nigeria attained its independence on the 1st October, 1960 it experienced numerous challenges of Nation-building, this is because, the conquest and imposition of colonial rule with its divide and rule tactics and other attendant consequences has set different ethnic groups in Nigeria at logger beads, mistrust has gained ground in the body polity of the Nation, couple with devastated economy, poor infrastructural facilitates. This informed the need for vibrant political parties in that critical period with good manifestoes to serve as check and balance instrument towards resolving Nigeria’s socio-economic challenges with a view to build a strong and prosperous Nation-state became imperative, therefore, this paper will examine the role of 196 0-1966 political parties in providing the required evaluation mechanisms in checkmating the excesses in democratic governance. The paper adopted the use of qualitative data obtained through; primary and secondary sources of information as well as the use of relevant existing literature. The paper finally established the impact of political parties in resolving some crisis of governance in the period under review.